The Influence of Family Support and Self Esteem of the Drug Abuse Prevention on Senior High School - Anggraini, Zelmi; Mudjiran, Mudjiran; Firman, Firman (Universitas Negeri Padang, 2021)
The aims of the study are to analyse influence of family support and self esteem on the prevention of drug abuse. The method of the study is quantitative method, using descriptive type. The population of the study are 2453 students, they are from senior high school of SMAN 1, 2, and 5 South Bengkulu, the sample are 301 students which is choose using proportional stratified random sampling technique, and the instrument used was questionnaire. The result of the study states that there is a significant relationship of family support and self esteem of the drug abuse prevention senior high school of SMAN 1, 2, and 5 South Bengkulu are 10,6%. The implication of the study can be use for making counseling quidance program of SMAN 1, 2, and 5 South Bengkulu.